Safety, efficacy and cost-effectiveness of outpatient versus inpatient joint arthroplasty: a systematic review and meta-analysis - Nikhil Ponugoti; Henry Magill (BMC Musculoskeletal Disorders)
Abstract Background The rise in the adoption of outpatient arthroplasty has been attributed to its cost-effectiveness, although safety concerns persist. In this meta-analysis, we compare inpatient and outpatient joint arthroplasty with a primary focus on readmission and complication rates, using exclusively high-quality prospective data. Cost-effectiveness was used as a secondary outcome measure. Methods A literature search was performed in Medline, Embase and Cochrane Library from inception to October 2023. A predefined strategy was used to conduct a systematic review and meta-analysis. Twelve studies were deemed eligible for inclusion. These were critically appraised using RoB analysis and MINORS criteria. Overall readmission rate, readmission rate for THA, readmission rate for TKA, complication rate and cost-analysis were selected as outcomes of interest. Forest plots were extracted using RevMan 5.3.5 software. Results The twelve studies included 2470 patients, of which 1052 were outpatients and 1418 inpatient subjects undergoing arthroplasty. Forest plot analysis showed no significant difference in safety outcomes (readmission and complication rates). However, there were significantly lower costs in the outpatient group compared to the inpatient group. The results of the analysis were; overall readmission rate (Odds ratio 0.66; P= 0.29; I2=18%), readmission rate in THA (odds ratio 0.62; P=0.10; I2=51%), readmission rate in TKA (odds ratio 0.67; P=0.56; I2=0%), overall complication rate (odds ratio 0.77; P=0.12; I2=38%) and cost analysis (RR -2.88; P<0.00001; I2= 93%). Conclusions This meta-analysis demonstrates that outpatient total joint arthroplasty (TJA) is a safe option, when compared to inpatient surgery. However, it is clear that further prospective studies and long-term randomized clinical data are necessary for a more comprehensive understanding.